2004
DOI: 10.1002/lsm.20002
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of alopecia areata with the 308‐nm xenon chloride excimer laser: Case report of two successful treatments with the excimer laser

Abstract: The use of the excimer laser is an effective, elegant, and safe means of treatment and has good tolerability. Analogous to topical treatment of alopecia areata, the immunosuppressive mechanism of the excimer laser can be interpreted as an induction of T-cell apoptosis. This new means of treatment has yet to be discussed in medical literature. Further studies with greater numbers are needed to assess its potential more precisely and evaluate the excimer laser in treating alopecia areata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 24 publications
2
38
1
3
Order By: Relevance
“…With this device, UVB can be irradiated to only one or a few individual patches, with adequate protection of the surrounding healthy skin. So far, there have been only a few studies [7,[17][18][19][20] on the use of excimer light therapy in AA.…”
Section: Rycina 7 Wyniki Leczenia W Zależności Od Czasu Trwania Chorobymentioning
confidence: 99%
See 2 more Smart Citations
“…With this device, UVB can be irradiated to only one or a few individual patches, with adequate protection of the surrounding healthy skin. So far, there have been only a few studies [7,[17][18][19][20] on the use of excimer light therapy in AA.…”
Section: Rycina 7 Wyniki Leczenia W Zależności Od Czasu Trwania Chorobymentioning
confidence: 99%
“…The choice of initial dose in most of the studies that have used a light source as a therapeutic modality is determined by MED [7,[17][18][19][20]. We, however, did not follow the MED protocol and chose an initial dose of 300 mJ/cm 2 without determining MED in our patients.…”
Section: Rycina 7 Wyniki Leczenia W Zależności Od Czasu Trwania Chorobymentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Recently, the use of biologics and laser therapy in alopecia areata have shown some beneficial results. [21][22][23] There has been a recent spurt in application of platelet-rich plasma (PRP) in dermatology and aesthetic medicine. 24 Overall, PRP seems to be a promising therapeutic modality but the level of evidence as of now, from the available published data is low.…”
Section: Introductionmentioning
confidence: 99%
“…16 With the discovery of AA as an autoimmune disorder with T cell-mediated inflammation of the hair follicle, 15 the use of excimer lasers has been suggested. Since the benefit of the excimer laser on AA first reported by Gundogan et al, 20 numerous studies have confirmed its efficacy. [21][22][23] The largest study so far was done on 18 patients with recalcitrant AA that involved the scalp, beard, arms and legs.…”
Section: -Nm Excimer Lasermentioning
confidence: 93%